UJI VALIDITAS ASPEK KOMPETENSI BERSASTRA PADA SOAL ULANGAN AKHIR SEMESTER GANJIL MATA PELAJARAN BAHASA INDONESIA KELAS VII TAHUN PELAJARAN 2012/ 2013 SMP NEGERI WILAYAH NGAWI BARAT - Rahmawati, Laili Etika; Kusumawati, Widya Puteri (Jurnal VARIDIKA, 2013)
The research has aim to examine the aspect validity of literary competance on the instrument test of the odd semester final examination in academic year 2012/2013 grade VII of the state junior high school in West Ngawi Region. The research was descriptive qualitative research, which related to the validity test of the instrument test item in the final examination. The data ceollected then analized of its validity by using the four language competence i.e. listening, speaking, reading, dan writing, and also analized based on its accordance level to the literary basic competence. The validity type which used on the research was the content validity which did not involve the statistic calculation at all except the rational analysis. The result data of the validity test was the qualitative data, i.e. the description of validity test to the odd semester final instrument test of state junior high school grade VII in academic year 2012/2013. The result of the research showed that the literary instrument test were more dominant on the writing competance aspect. It is proof on the presence of tendency to include the other competence (such as listening competence) in the writing activity. Furthermore, on the writing basic competence, the ways to demonstrate to the students were more efficient and varies so that the instrument was appropriate to be applied. On the literary aspect of instrument test, there was one of the basic competence which did not included to the instrument test, i.e. basic competence of 8.2 rewrite the fairytale using the own language of the fairytale which had ever read or listened. As the research forward, this basic competence do not listed on the literary aspect of the instrument test.